Development of VLPs (like particle virus) as potential recombinant vaccine against dengue virus (DENV) (Research, Society and Development, 2023)
Dengue is a serious disease, the eradication of which has not yet been achieved in much of the world. The absence of an effective and promising vaccine to prevent the disease is one of the main factors contributing to this situation. The development of Virus Like Particles (VLPs) has proven to be a promising strategy in the search for an effective vaccine against Dengue. According to the literature, dengue is characterized as one of the main public health problems worldwide. Thus, it is described as an infectious disease considered the main arbovirus that affects humans today. However, no specific treatment or vaccine is currently available on the market. Therefore, the production of a multivalent vaccine capable of inducing an immunological response against the four serotypes of the virus (DENV) would be the best option for preventing the disease. Considering that virus-like particle (VLP) vaccines have achieved positive results in preventing other contagious diseases, it is possible to question whether this type of vaccine would not be effective if applied to dengue prevention. Given this scenario, we can understand and justify the importance of this work, since studies on the application of VLP in the prevention of dengue can help in the development of new methods of controlling this disease.